Advances and challenges in novel drug delivery systems for glioma therapy - Ma, Peipei; Li, Yongkang; Gu, Yingrui; Zeng, Hui; Xiang, Hongwei; Cao, Zhenzhen; Han, Yankun; Cui, Yong; Liu, Haixiao (Frontiers in Pharmacology, 2025)
Glioma therapy faces substantial challenges primarily due to the restrictive nature of the blood-brain barrier (BBB), limiting effective drug penetration and reducing therapeutic efficacy. Recent advancements in novel drug delivery systems (DDS), including exosome-mediated carriers, drug conjugates, and ultrasound-assisted delivery, have demonstrated promising results in overcoming these limitations. Exosomes offer superior biocompatibility, efficient BBB crossing, and natural cellular targeting capabilities; drug conjugates enable highly selective drug delivery through tumor-specific ligands; and ultrasound-assisted systems transiently disrupt the BBB to permit greater drug entry. Despite encouraging preclinical and early clinical outcomes, significant translational barriers remain. Challenges such as exosome manufacturing scalability, conjugate stability, and immunogenicity, as well as the optimization of ultrasound protocols, must be thoroughly addressed to achieve clinical translation. Overcoming these hurdles requires ongoing multidisciplinary collaboration and rigorous clinical evaluation. Continued progress in refining these innovative DDS approaches holds the potential to markedly improve therapeutic outcomes and patient prognosis in glioma treatment.